Human Vital-Sign Measurement Using Non-Invasive and Non-Destructive Optical Detection Technique - KHAIRUDDIN, AHMAD SYAUQI (2017)
Optical sensors had play a significant role in various study field and industry. Today, there is an increasing demand for optical sensors in the development smart wearables for health tracking purposes such as heart rate (HR) and oxygen saturation level in blood (SpO2) monitoring. However, current design is meant to be used in a static environment where in real situation people uses these wearables to track their HR continuously especially in motion. Pulse Oximeter is a device that utilizes optical technology to measure HR and SpO2 in blood. It works by estimating the amount of light absorbance by the hemoglobin in blood cell when the light is propagating from the source to the detector via two different methods which are transmittance and reflectance. Despite its potential as a non-invasive technique to measure the mentioned parameters, the device faced a challenge when used in presence of motion which is known as the Motion Artifact (MA). The noise generated by motion simply makes the measurement unreliable and inaccurate especially when the device is to be used on athletes and patients that moves a lot. In fact, most of smart wearable is not designed for static use because it does not have capability to eliminate MA. This project is to study how the presence of motion is affecting the measurement by taking HR reading and PPG signals on several different movement sets. Then, an extensive analysis is to be performed to find relationship between different motion types and the motion artifact magnitude on the reading. The results show that amplitude of PPG signals is sensitive to x and zdirection motion with 68.95% and 121.15% variation respectively. The heart rate also is varied by 47.63% and 38.24% when compared to resting state. For random motion, it was observed that the heart rate for shaking wrist, sit and stand, and running activities are varied significantly by 85.73%, 85.71% and 66.67% respectively. In terms of amplitude range, only sit and stand, walking and running are sensitive to motion which shows variation of 5.10%, 22.13% and 48.70% compared to resting state. Lastly, a similar heart rate variation is observed for different sensor levels relative to heart position. However, the PPG amplitude is significantly different for sensor below heart position which may be due to swelling of vein when the blood pressure increases.